2021
DOI: 10.1063/5.0044066
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid optoelectronic Mott insulator

Abstract: The coupling of electronic degrees of freedom in materials to create "hybridized functionalities" is a holy grail of modern condensed matter physics that may produce versatile mechanisms of control. Correlated electron systems often exhibit coupled degrees of freedom with a high degree of tunability which sometimes lead to hybridized functionalities based on external stimuli. However, the mechanisms of tunability and the sensitivity to external stimuli are determined by intrinsic material properties which are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Layer thicknesses were controlled in situ by a quartz microbalance and later confirmed by X-ray reflectometry (XRR) for each reference sample of the continuous film (Figure c). The profile fitting of the XRR measurements was made with the Parrat 32 code, which presents well-defined thicknesses with an interlayer roughness of less than 1.3 nm. The asymptotic dependence of the interface roughness with spacer thickness implies that the interlayer coupling is not affected by dipolar interaction or interface roughness .…”
Section: Methodsmentioning
confidence: 99%
“…Layer thicknesses were controlled in situ by a quartz microbalance and later confirmed by X-ray reflectometry (XRR) for each reference sample of the continuous film (Figure c). The profile fitting of the XRR measurements was made with the Parrat 32 code, which presents well-defined thicknesses with an interlayer roughness of less than 1.3 nm. The asymptotic dependence of the interface roughness with spacer thickness implies that the interlayer coupling is not affected by dipolar interaction or interface roughness .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we showed that in a judiciously designed bilayer that contains two materials with no apparent similarity: a photosensitive semiconductor CdS and a strongly correlated Mott insulator, displays such kind of novel functionality. 224 While the Mott insulator itself has very little response to electromagnetic radiation (light), when the two are adjacent one can see a dramatic effect of shining light: the Mott metal-insulator transition is completely suppressed. As it pertains to neuromorphic systems, the Mott insulator in question here has also shown to have spiking behavior in the right conditions.…”
Section: A Perspectives For Individual Neuromorphic Quantum Devicesmentioning
confidence: 99%
“…52,54 Our preliminary results have shown that, by combining it with photoactive materials, the metal-to-insulator transition temperature of VO 2 can change dramatically under sunlight exposure, illustrating a strong photo response. 224 This response is largely due to the Mott nature of VO 2 , where the electron/hole doping originating from the photoactive materials strongly influences its physical properties. Indeed, studies have shown that vanadium oxide devices can be used to store energy locally as concentration cells.…”
Section: A Perspectives For Individual Neuromorphic Quantum Devicesmentioning
confidence: 99%
“…Vanadium dioxide is one of the most promising materials with such properties due to its temperature-driven phase transition near room temperature (68 °C). [1][2][3][4][5] Great optical and resistance changes coupled with MIT, reversibility, and high speed of transformation are advantages of this material. [6][7][8] In addition, the possibility of changing the MIT temperature by the action of several other external stimuli makes it possible to design many electronic devices in which vanadium dioxide can be used as the core functional material.…”
mentioning
confidence: 99%
“…Their favorable differences are a convenient form factor, the ability to influence the transition parameters by choosing a substrate, and the great convenience of obtaining a purer epitaxial VO 2 film by using a structurally coherent substrate. All the most popular physical methods such as pulsed laser deposition (PLD), 3,7,12,13 magnetron sputtering, 4,5,7,14 ion beam deposition, [15][16][17] and molecular-beam epitaxy [18][19][20] were adapted for obtaining VO 2 films.…”
mentioning
confidence: 99%